2010
DOI: 10.1021/es903936m
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Separation for Recycling Waste Printed Circuit Board: A Study on External Factor and a Robust Design for Optimization

Abstract: Electrostatic separation is an effective and environmentally friendly method for recycling waste printed circuit board (PCB) by several kinds of electrostatic separators. However, some notable problems have been detected in its applications and cannot be efficiently resolved by optimizing the separation process. Instead of the separator itself, these problems are mainly caused by some external factors such as the nonconductive powder (NP) and the superficial moisture of feeding granule mixture. These problems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…The high concentration (500 g L À1 ) and the low concentration (50 and 5 g L À1 ) of metals were used to respectively simulate the solvent-based separation of BFRs from metallic and plastic fractions obtained from WEEE via mechanical processing. Note that the metallic fractions may contain 12-18% plastics (Hou et al, 2010) whereas the plastic fractions may contain >1% metals (Ernst et al, 2000;Schlummer et al, 2006). Since Zn and Cu were the major metal components of WEEE (Huang et al, 2009), Zn and Cu at different concentrations (50 and 5 g L À1 ) were used for elucidating the dosage effects on the transformation rate of TBBPA.…”
Section: Batch Reaction Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high concentration (500 g L À1 ) and the low concentration (50 and 5 g L À1 ) of metals were used to respectively simulate the solvent-based separation of BFRs from metallic and plastic fractions obtained from WEEE via mechanical processing. Note that the metallic fractions may contain 12-18% plastics (Hou et al, 2010) whereas the plastic fractions may contain >1% metals (Ernst et al, 2000;Schlummer et al, 2006). Since Zn and Cu were the major metal components of WEEE (Huang et al, 2009), Zn and Cu at different concentrations (50 and 5 g L À1 ) were used for elucidating the dosage effects on the transformation rate of TBBPA.…”
Section: Batch Reaction Experimentsmentioning
confidence: 99%
“…Selective disassembly and mechanical processing (e.g., shredding, magnetic, density-based and eddy current separation) can separate the metalrich fractions from the plastic fractions. Subsequently, the metallic fractions, which often contain 12-18% of plastics (Hou et al, 2010), are further upgraded in incinerators or melting furnaces to recover pure metals, and the plastic fractions are thermally treated to allow the recovery of gases, oils and chars as fuels or feedstocks. It is highly desirable to remove BFRs before thermal processing (e.g., incineration, combustion, and pyrolysis) of both metal-rich and plastic fractions because BFRs can form polybrominated dibenzop-dioxins/dibenzofurans (PBDDs/Fs) and other toxic brominated phenols (Wichmann et al, 2002;Barontini et al, 2004;Marongiu et al, 2007) at relatively high temperature conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Park et al 140 found that electrostatic separators were efficient for segregating mixed plastics using a two-stage separation process. Hou et al 141 observed a reduction in effectiveness in the separation process because of the presence of nonconductive powder and moisture in the WEEE. Consequently, Hou et al 141 suggested using cyclone separators to effectively manage the granule particle size and remove nonconductive powder before processing in the electrostatic separator.…”
Section: Separation Technologiesmentioning
confidence: 99%
“…Water content in biowaste decides its conductivity and likelihood to be moved to the right-most tank. However, this parameter is hard to control in practical conditions [27]. The size of granules, on the other hand, varied due to the machinery limitation.…”
Section: Introductionmentioning
confidence: 99%